Konsep Ketuhanan dalam Agama-Agama dan Implikasinya terhadap Pandangan Dunia Islam - Marini, Melani Ida; Istikotimah, Istikotimah; Jauhara, Ratna; Sumiran, Sumiran (TSAQOFAH, 2026)
This study analyzes the concept of divinity across various religious traditions and its implications for shaping the Islamic worldview. It aims to critically examine how the concept of tauhid in Islam is constructed through theological dialogue with concepts of God in other religions, and to explain its epistemological, ontological, axiological, and practical consequences for the Islamic worldview. The research employs a comparative theology approach by analyzing primary sources (the Al-Qur’an, Hadis, and the Alkitab) alongside relevant secondary literature from classical and contemporary scholars. The findings indicate that the Islamic concept of divinity, which is centered on tauhid and the declaration lā ilāha illā Allāh, is not merely a theological statement but a paradigm that structures every aspect of Muslim life, including ways of understanding reality, values, and human action. Compared with concepts of divinity in Judaism, Christianity, and Zoroastrianism, fundamental differences lie in the understanding of divine simplicity, the configuration of God’s attributes, and the relationship between divine transcendence and immanence. The implications of the Islamic concept of divinity for the worldview include: (1) affirmation of Allah’s absolute sovereignty in the creation and governance of the universe, (2) a distinct understanding of human will and destiny (qadar), (3) reinforcement of the principle of divine justice and human moral responsibility, and (4) the formulation of human life’s purpose as servants who worship sincerely. This study contributes to deepening Islamic theology and reaffirms the relevance of the Islamic concept of divinity for shaping a meaningful worldview in the context of modern life.